2017
DOI: 10.1111/1365-2745.12798
|View full text |Cite
|
Sign up to set email alerts
|

The effects of climate warming and disturbance on the colonization potential of ornamental alien plant species

Abstract: (2017) 'The eects of climate warming and disturbance on the colonization potential of ornamental alien plant species.', Journal of ecology., 105 (6). pp. 1698-1708. Further information on publisher's website:https://doi.org/10.1111/1365-2745.12798 Publisher's copyright statement: This is the accepted version of the following article: Haeuser, E., Dawson, W. van Kleunen, M. (2017). The eects of climate warming and disturbance on the colonization potential of ornamental alien plant species. Journal of Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 55 publications
3
50
1
Order By: Relevance
“…Growth form, vegetative propagation, propagation by seeds and hardiness were not significant in any model. Some of these species characteristics, however, have been found to affect naturalisation or invasion success in studies focussing on smaller regions (Haeuser, Dawson, & van Kleunen, ; Hanspach et al., ; Kolar & Lodge, ; Maurel et al., ). The absence of significance in our study might reflect potential correlations with factors retained in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Growth form, vegetative propagation, propagation by seeds and hardiness were not significant in any model. Some of these species characteristics, however, have been found to affect naturalisation or invasion success in studies focussing on smaller regions (Haeuser, Dawson, & van Kleunen, ; Hanspach et al., ; Kolar & Lodge, ; Maurel et al., ). The absence of significance in our study might reflect potential correlations with factors retained in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The 25 non-native species used were herbaceous ornamental plants, either annual or perennial, commonly cultivated in European gardens. They are all alien to Europe and not naturalized there, but often naturalized outside of Europe (Table 1; see Dullinger et al, 2017;Haeuser, Dawson, & van Kleunen, 2017 for details on species selection criteria). At the same time that the natives were sown in the pots, non-native ornamentals were sown F I G U R E 1 Trait shifts, biotic resistance and trait hierarchical position.…”
Section: Experimental Designmentioning
confidence: 99%
“…For example, a recent meta‐analysis showed that invasive alien plants take more advantage of CO 2 enrichment and climate warming than native species (Liu et al, ). On the other hand, many alien plant species that do not pose an invasion risk under current environmental conditions may become invasive under future conditions with ongoing global environmental change (Dullinger et al, ; Haeuser et al, ; Walther et al, ). Numerous empirical studies have tested how invasive plants interact with other environmental changes, but almost all of these studies considered only environmental changes in mean conditions (Leishman & Thomson, ; Liu et al, ; Jia et al, ; Manea & Leishman, ; but see Liu & van Kleunen, ; Parepa, Fischer, & Bossdorf, ).…”
Section: Introductionmentioning
confidence: 99%